The connection between prospective teachers’ procedural and conceptual knowledge with problem-posing skills of fractions - Yesi Martha Afrillia; Zetra Hainul Putra; Eddy Noviana; Riyan Hidayat; Dahnilsyah Dahnilsyah (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study examined the connections between procedural and conceptual knowledge of addition and subtraction of fractions with the problem-posing skills of prospective primary teachers. The applied method was a correlational study with structural equation modeling-partial least square (SEM-PLS) analysis. The sample in this research was 101 third-year students from a primary teacher education study program of a public university in Riau, Indonesia. The results showed that prospective primary teachers have high procedural knowledge and problem-posing skills on addition and subtraction. However, they have poor performance on problems related to conceptual knowledge of addition and subtraction of fractions. Then, the results also revealed a significant connection between procedural and conceptual knowledge with problem-posing skills on addition and subtraction of fractions of prospective primary teachers. Improving prospective primary teachers’ procedural and conceptual knowledge could raise their problem-posing skills on adding and subtracting fractions.